2020
DOI: 10.1136/annrheumdis-2020-eular.4824
|View full text |Cite
|
Sign up to set email alerts
|

Ab0318 characteristics of Patients With Rheumatoid Arthritis Who Have Withdrawn the Last Biological Drug: Real-Life Results From a Local Registry

Abstract: Objectives:To assess the characteristics of patients with rheumatoid arthritis (RA), who have withdrawn the last biological drug (bDMARD), and to know the reasons for withdrawal of treatment.Methods:Retrospective and cross-sectional study on December 31, 2019, of patients with RA, treated with any of the bDMARDs, including JAK (JAKi) inhibitor drugs, commonly used, from 1/1/2000 to 12/31/2019. General data were collected from patients, and RA: time of evolution, presence of rheumatoid factor (RF) and anti-citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Other studies reported data, such as that of Reed et al (32) based on the registry of Corrona (402 patients, 238 in monotherapy and 164 in combination treatment), and Mueller et al (36), based on the records of the hospitals of St. Gallen and Aarau in Switzerland. In general, all the studies showed a higher percentage of women, and the mean age of the patients was very similar, between 48 and 61 years (43,44). Nevertheless, compared to the Australian study by Bird et al (35), with ages ranging between 55 and 74, Spanish RA patients treated with tofacitinib are younger in that series (median age ranges 61-62,9 and ages range 40-74.4), and in the BIOBADASER 3.0 the mean age of patients treated with JAK inhibitors was 59.6 (12.3 SD) (54).…”
Section: Integration Of the Real-world Evidencementioning
confidence: 79%
See 3 more Smart Citations
“…Other studies reported data, such as that of Reed et al (32) based on the registry of Corrona (402 patients, 238 in monotherapy and 164 in combination treatment), and Mueller et al (36), based on the records of the hospitals of St. Gallen and Aarau in Switzerland. In general, all the studies showed a higher percentage of women, and the mean age of the patients was very similar, between 48 and 61 years (43,44). Nevertheless, compared to the Australian study by Bird et al (35), with ages ranging between 55 and 74, Spanish RA patients treated with tofacitinib are younger in that series (median age ranges 61-62,9 and ages range 40-74.4), and in the BIOBADASER 3.0 the mean age of patients treated with JAK inhibitors was 59.6 (12.3 SD) (54).…”
Section: Integration Of the Real-world Evidencementioning
confidence: 79%
“…The mean duration on biologic therapy before switching was 3.9 years (range: 1.2-10.9 years). In the second study, the mean time in treatment with a bDMARD was 2.6 years (SD: 3.0 years) (44). The reasons to switch therapy in 81/252 patients were: loss of efficacy (25/81, 30.9%); AEs (31/81, 38.3%); change of address/loss of follow-up (20/81, 24.7%); and voluntary abandonment of treatment by the patient (5/81, 6.2%).…”
Section: Baseline Disease Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations